Pengaruh Persepsi Kegunaan dan Persepsi Kemudahan Terhadap Loyalitas Dengan Kepuasan Sebagai Variabel Intervening dalam Menggunakan BSI Mobile - Pasaribu, Mahmud; Hasibuan, Abdul Nasser; Cahyani, Utari Evy (ITB AAS INDONESIA Surakarta, 2024)
The purpose of this study was to determine how the perceived usefulness and convenience affect customer loyalty either directly or through customer satisfaction. The discussion of this research is related to the TAM (technology acceptance model) analysis, where researchers can find out what things are phenomena in BSI Kc customers. Padangsidimpuan customers in using the BSI Mobile application. This research is quantitative research. The sample of this study was 371 samples. The data collection instrument used a closed questionnaire to BSI Kc customers. Padangsidimpuan customers who use the BSI Mobile application. Data analysis using inner model, outer model, and intervening hypothesis testing. Based on the results of the study, it is known that customer satisfaction can explain customer loyalty by 0.363 or 36.3 percent, while 63.7 percent is influenced by other variables outside of this study. The loyalty has an R2 value of 0.368 or 36.8 percent, while 63.2 percent is influenced by other variables in this study. Then there is an influence between the usefulness and ease of using the BSI Mobile application on customer satisfaction. There is an influence between the usefulness and ease of using the BSI Mobile application on customer loyalty. There is no influence between customer satisfaction using the BSI Mobile application on customer loyalty. Customer satisfaction does not mediate the usefulness and ease of using the BSI Mobile application on customer loyalty at BSI Kc. Padangsidimpuan.